Aktivitas antelmintik kulit buah Delima Merah (Punica granatum) dan jus buah Delima Merah (Punica granatum ) pada hewan coba kelinci - Erna Kristinawati; Erlin Yustin Tatontos; Zainal Fikri; Urip Urip (Postgraduate, University of Mataram, 2023)
Traditional medicines from plants (herbs) are less effective due to inappropriate doses for treatment, but are relatively safe from side effects. The purpose of this study was to determine the anthelmintic activity of red pomegranate peel extract and red pomegranate juice in rabbits as experimental animals. This research is experimental research using Completely Randomized Design (CRD) and Post Test Only Control Design approach. The population for this study were rabbits (Orytolagus cuniculus), the sample for this study were 9 rabbits aged 4-5 months with a body weight of 1.5 kg - 2 kg which were divided into two treatment groups and one control group. The results of anthelmintic activity of red pomegranate peel extract (Punica granatum L) with a dose of 100 mg/ml an average activity of 43.01%, a dose of 150 mg/ml an average activity of 100% and a dose of 200 mg/ml an average activity of 50, 9%. The results of the anthelmintic activity of red pomegranate juice (Punica granatum L) with a dose of 1 ml / kg/BW an average activity of 100%, a dose of 5 ml / kg/BW an average activity of 91.67% and a dose of 10 ml /kg/ BW average activity 58.69%.